VACUUM - EXTRACTION OF THE FETUS BY DIFFERENT METHODS (Academicia Globe: Inderscience Research, 2022)
The article provides a comparative analysis of the vacuum-extraction of 30 patients for the period 2019-2021. The study was conducted on the basis of the 1st clinic of the Samarkand State Medical University. Vacuum - extraction of the fetus using a Kiwi vacuum extractor has more favorable outcomes, unlike the classic one.